Do you see what happens around you? Men's Perceptions of Gender Inequality in Software Engineering - Canedo, Edna Dias; Soares, Larissa; Silva, Geovana Ramos Sousa; Santos, Verônica Souza Dos; Mendes, Fabiana Freitas (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
Context: It is known that men practitioners are predominant in software development teams over women. In recent years, researchers have investigated gender inequality from different perspectives, such as gender bias and suggestions to increase diversity in development teams. However, while most of the existing literature investigates the perception of women practitioners, the vast majority of the software development workforce – men – has received less attention. Goal: This work investigates men’s perceptions of gender inequality in software development teams and their experiences compared in software development to women. Method: Our study conducted a survey with 217 male practitioners, using a questionnaire consisting of 27 questions. The collected data was analyzed using a combination of quantitative and qualitative techniques, including graphical representations, percentages, and the grounded theory methodology. Results: Our findings reveal that most men do not perceive any sexist behavior among their team members and they are satisfied with the performance of their functions. In addition, their main suggestions to increase their participation in software development projects are offering training courses and improving the interaction among team members. Conclusions: The barriers and challenges that men practitioners face in software development teams are not the same as those faced by women. In addition, they consider that women do not work in software development due to a lack of affinity and knowledge about coding.